Mariategui, clarte's subscriber Mariátegui, assinante de clarté - Tornquist C.S.* (2019)
© 2020 Universidade Estadual Paulista.This article analyzes the dialogue between Jose Carlos Mariategui and Clarte movement, a group of French intellectuals who, between 1919 and 1928, the distribution of which crossed the boundaries of the Frenchspeaking countries. In addition to direct references to the group and the sharing of themes and common authors, Mariategui translated and published articles edited by Clarte, expressing a common practice at the time: the permanent exchange and interlocution between and by the journals, consolidating a public sphere of intense and dynamic debate. This process consolidated an editorial network of international character, articulating South America with the world, what was fundamental in the organization of culture, a task Mariategui assumed as a priority when returning from his trip to Europe.